2007
DOI: 10.1016/j.jneuroim.2007.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Antigen presenting cells treated in vitro by macrophage colony-stimulating factor and autoantigen protect mice from autoimmunity

Abstract: Macrophage colony-stimulating factor (M-CSF) is a critical cytokine in the development of monocytic lineage and may have immunoregulatory properties. Here we show that peritoneal antigen presenting cells (APCs) treated with M-CSF produced decreased levels of proinflammatory cytokines IFN-γ, TNF-α and IL-12. These APCs treated with M-CSF + autoantigen peptide significantly suppressed antigen-specific T cell proliferation, induced regulatory CD4 + and CD8 + T cells in vitro and in vivo, and significantly suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Moser (78) also reported that Ag-pulsed macrophages could generate primed T cells in vivo but, in comparison to DC, selectively activated Th2 responses. Finally, extending the discussion above of macrophage-mediated suppression, Guan et al (79) reported that CSF-1-treated peritoneal macrophages exerted Ag-specific suppression of alloreactivity and autoimmune responses in mice.…”
Section: Macrophages Can Present Ag In a Primary Responsementioning
confidence: 64%
“…Moser (78) also reported that Ag-pulsed macrophages could generate primed T cells in vivo but, in comparison to DC, selectively activated Th2 responses. Finally, extending the discussion above of macrophage-mediated suppression, Guan et al (79) reported that CSF-1-treated peritoneal macrophages exerted Ag-specific suppression of alloreactivity and autoimmune responses in mice.…”
Section: Macrophages Can Present Ag In a Primary Responsementioning
confidence: 64%
“…The APCs used in our study and in the studies described above all direct T cells to produce less IFN-␥ [38,40,41]. However, in contrast to myelin-laden macrophages, the tolerogenic APCs used in the other studies skew T cells to produce increased IL-10 levels [38,40] and decreased IL-17A levels [40]. Despite decreased IL-10 and unaffected IL-17A production by myelin-laden macrophage-activated T cells, myelinladen MOG-pulsed macrophages could still suppress EAE.…”
Section: Figure 6 Endogenous Myelin Antigens Do Not Elicit Myelin-spmentioning
confidence: 98%
“…Cells were washed with PBS and resuspended in RPMI 1640 supplemented with 10% FBS. We have previously shown that this preparation procedure yielded > 95% pure CD11b + CD11c − macrophages with only 1.8% CD11c + DCs (Guan et al, 2007). …”
Section: Methodsmentioning
confidence: 95%
“…Our present study shows for the first time the mechanism by which MOG i.v. also exerts its modulatory effects on CD11b + CD11c − peritoneal macrophages (Guan et al, 2007) and splenic macrophages (Throsby et al, 1991; Throsby et al, 1993). MOG i.v.…”
Section: Discussionmentioning
confidence: 99%